Immature Platelets in Hematologic Malignancies: A Meta-Analysis - Mirna Fauziah Lailly; Thariq Ahmad; Essa Loyalita Lestari (Global Writing Academica Researching and Publishing, 2025)
Thrombocytopenia is a common hematological complication in patients with malignant hematological diseases, particularly after chemotherapy or hematopoietic stem cell transplantation (HSCT). This condition increases the risk of bleeding and necessitates strict hematological monitoring and platelet transfusions. Immature Platelet Fraction (IPF), a parameter reflecting thrombopoiesis, has emerged as a potential biomarker for predicting platelet recovery. This meta-analysis evaluates the role of IPF and IPF% in predicting platelet recovery in patients with hematological malignancies post-chemotherapy and HSCT. A systematic literature search was conducted across multiple databases, including PubMed, EMBASE, and Cochrane Library, from 2014 to 2024. Studies were selected based on predefined criteria, including patient population, intervention, and outcomes related to platelet recovery. The analysis revealed that IPF% increases earlier than other hematological parameters, with a peak occurring 1–11 days before platelet recovery. However, significant heterogeneity (I² = 99%) was observed among studies, indicating variability in methodologies and patient populations. Despite promising results, the clinical application of IPF% requires further validation to establish optimal cutoff values and standardize measurement techniques. This meta-analysis highlights the potential of IPF% as a predictive biomarker for platelet recovery, while emphasizing the need for more robust studies to enhance its reliability in clinical practice.